2014
DOI: 10.3390/nu6125619
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Spanish Version of the Three-Factor Eating Questionnaire-R18 (Tfeq-Sp) and Its Relationship with Some Eating- and Body Image-Related Variables

Abstract: The aims of this study were to analyze the psychometric properties of the Spanish version of the Three-Factor Eating Questionnaire-R18 (TFEQ-SP), as well as determine its validity by evaluating the relationship of the TFEQ-SP with different parameters related to body mass index, weight perception, perception of physical fitness, self-esteem, and food intake, as well as with weight control-related variables. A total of 281 participants (aged 18.38 ± 6.31) were studied. The factor analysis yielded three factors:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 39 publications
7
71
1
6
Order By: Relevance
“…The concept of cognitive restraint has been mostly explored in the context of obesity [11,12]. Existing research provides evidence that cognitive restraint is greater among overweight and obese individuals compared to underweight and normal weight individuals [4,16]. Overall, the higher the body mass index (BMI) and body fat mass, the stronger the tendency towards these restrictions [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The concept of cognitive restraint has been mostly explored in the context of obesity [11,12]. Existing research provides evidence that cognitive restraint is greater among overweight and obese individuals compared to underweight and normal weight individuals [4,16]. Overall, the higher the body mass index (BMI) and body fat mass, the stronger the tendency towards these restrictions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the disinhibition related to eating is associated with BMI [18]. However, two studies reported no difference in uncontrolled eating between people with abnormal body weight (underweight, overweight and obesity) and normal weight [4,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To measure dietary restraint the cognitive restraint of eating subscale of the Three-Factor Eating Questionnaire-R18 (TFEQ) was used (English version: Stunkard & Messick, 1985; Spanish version: Jauregui-Lobera, Garcia-Cruz, Carbonero-Carreño, Magallares, & Ruiz-Prieto, 2014). This subscale comprises of 6 items on a 4-point response scale (definitely true -1-, mostly true -2-, mostly false -3-, definitely false -4-).…”
Section: Instrumentsmentioning
confidence: 99%